Chemically delaminated free-standing ultrathin covalent organic nanosheets - Khayum, M. Abdul; Kandambeth, Sharath; Mitra, Shouvik; Nair, Sanoop B.; Das, Anuja; Nagane, Samadhan S.; Mukherjee, Rabibrata; Banerjee, Rahul (Angewandte Chemie-International Edition, 2016)
Covalent organic nanosheets (CONs) are a new class of porous thin two-dimensional (2D) nanostructures that can be easily designed and functionalized and could be useful for separation applications. Poor dispersion, layer restacking, and difficult postsynthetic modifications are the major hurdles that need to be overcome to fabricate scalable CON thin films. Herein, we present a unique approach for the chemical exfoliation of an anthracene-based covalent organic framework (COF) to N-hexylmaleimide-functionalized CONs, to yield centimeter-sized free-standing thin films through layer-by-layer CON assembly at the air-water interface. The thinlayer fabrication technique presented here is simple, scalable, and does not require any surfactants or stabilizing agents.